Project cost estimation techniques used by most emerging building contractors of South Africa - Seeletse, Solly; Ladzani, Watson (University of the Free State, 2012)
This article investigates newly emerging building contractors of South Africa who are expected to survive by projects obtained mainly through tendering. Some of these contractors fail even before obtaining the first tender while many fail in the first three years of their formation. The research population used was restricted to formally registered businesses found at the time in the register of the Construction Industry Development Board (cidb). The population of 792 businesses, registered as Grade 5 class, consisted of five distinct types of contractors, general builders, civil engineers, electricians, mechanical builders and other sundry players. A sample of 160 was used which is approximately 20% of the population. The literature was reviewed on tendering and related aspects: competitive bidding, estimating activities, pricing a tender, and evaluating a tender. The research tool used was a questionnaire, which investigated biographical and company information, proposal management and estimation, programming and scheduling, estimating strategies, understanding of basic cost concepts, project risk management, pre-tender internal price evaluation, and tender submission. Findings of this research revealed that South African emerging contractors showed inadequacies and variations in cost concepts, scheduling tools, risk management and tender price estimation. They also lacked essential resources and skills for competing for tenders. Emerging contractors are advised to use consultants to assist them and/or subcontract to established contractors with a reputable history. They should use these opportunities to learn superior estimation methods (which are also more complex) and apply them to improve their own tendering practices.

moet oorleef op projekte wat hoofsaaklik deur tenders verkry word. Sommige van hierdie kontrakteurs raak bankrot nog voordat hulle die eerste tender gekry het, terwyl baie bankrot speel binne die eerste drie jaar van hul ontstaan. Die navorsingspopulasie wat gebruik is, was beperk tot formeelgeregistreerde besighede wat toe gevind kon word in die register van die Konstruksie Industrie Ontwikkelingsraad (Construction Industry Development Board Die populasie het bestaan uit 792 besighede, geregistreer as graad 5-klas, bestaande uit vyf afsonderlike tipes kontrakteurs, algemene bouers, siviele ingenieurs, elektrisiëns, meganiese bouers en diverse rolspelers. ‘n Monster van 160 is gebruik, wat ongeveer 20% van die populasie is. Die literatuur is nagegaan oor om vir iets te tender en verwante aspekte: mededingende bie, voorleggingsbestuur, beramingsaktiwiteite, risikobestuur, prys van ‘n tender en evaluering van ‘n tender. Die navorsingsinstrument wat gebruik is, was ‘n vraelys wat die biografiese en maatskappyinligting ondersoek het, naamlik voorleggingsbestuur en beraming, programmering en skedulering, beramingstrategieë, begrip van basiese kostekonsepte, projek risikobestuur, voor-tender interne prysevaluasie en tendervoorlegging. Bevindinge van hierdie navorsing het getoon dat Suid-Afrika se ontluikende kontrakteurs ontoereikendhede en variasies in kostebegrippe, skeduleringsinstrumente, risikobestuur en in tenderprysskatting toon. Hulle het ook ‘n gebrek aan noodsaaklike hulpmiddele en die vermoëns om mee te ding vir tenders. Daar word aanbeveel dat ontluikende kontrakteurs konsultante moet gebruik om hulle by te staan en/of dat hulle moet subkontrakteer by gevestigde kontrakteurs wat ‘n hoog aangeskrewe reputasie het. Hulle moet hierdie geleenthede gebruik om uitmuntende beramingsmetodes (wat meer ingewikkeld is) te leer en toe te pas om hul eie tenderpraktyke te verbeter.
Keywords: Cost estimation; Estimation methods; Emerging contractors; Tender